Assessment of the President of BEM Using the Weighted Product Method at XYZ University - Tundo, Tundo; Nugroho, Agung Yuliyanto; Saidah, Andi (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2025)
The election of the BEM President is a hereditary tradition at XYZ University every year. This election was carried out to find a leader who has a firm personality and broad insight. As the number of students at XYZ University increased, we doubled the election using the Weighted Product (WP) method with the conditions that we had determined with the campus. So we are sure that this method will produce the leaders we expect, and also in this way the campus automatically saves budget for voting or direct elections. The WP method which is quantitative in decision making, the WP method uses multiplication to link attribute ratings, where the rating of each attribute must be raised to the first power of the attribute weight in question. By applying the WP method to decision support system, then implementing it into a ranking system, it will produce students who deserve to become BEM in the next period. There is a WP method at XYZ University in order to get a BEM President who meets the criteria we set. Where the existing criteria consist of TPA criteria, Liveliness, Commitment, GPA, Absent, and Age. After calculating using the WP method, it was found that the strongest student who deserved to be president of BEM was Siti Munawaroh who was ranked first. The results of the recommended method by conducting a questionnaire to the BEM management by producing an accuracy of 0.01356.